Isolation and characterization of mesophile pla-degrading bacteria from landfill soil - Joyce Cynthia, Jalani (2023)
Polylactic acid (PLA) is a biopolymer introduced as an alternative to petroleum-based plastics. However, when PLA is discarded in landfills, it will not degrade entirely because it is optimally degraded in thermophilic conditions. Therefore, the isolation and characterization of PLA-degrading bacteria from landfill soil were conducted. The objectives of this study were to isolate and characterize PLA-degrading bacteria from local landfill soil at mesophilic temperature. The soil sample was collected from a landfill site in Pekan, Pahang, and the isolation process was done via serial dilution up to a dilution factor (DF) of 10-10. The results revealed that two isolates, designated as B8A and A10B, were selected and identified as Brevibacillus parabrevis and Renibaterium salmoninarum, respectively. From the results, both isolates were further characterized in this study. The characterization of bacterial isolates was conducted through morphological studies, Gram staining, the catalase test, the presence of the protease enzyme, and relative enzyme activity. Isolate B8A has punctiform morphological characteristics, including a flat elevation and a curled margin. In comparison, isolate A10B was morphologically characterized as having a circular form, flat elevation, and entire margin. Isolates B8A and A10B were also gram-positive and catalase-positive. When streaked on skim milk agar, both isolates displayed halo zone formation, confirming the presence of the protease enzyme secreted by the bacteria. A10B showed a high relative enzyme activity of 3.86, while isolate B8A is slightly lower at 1.33. Isolates B8A and A10B were further characterized by observing the growth curves and enzyme activities for protease, lipase, and amylase enzymes. For the enzyme assays, the protease enzyme shows the highest activity at 120.45 ± 1.04 U/mL and 114.49 ± 0.37 U/mL for isolates A10B and B8A, respectively. Meanwhile, lipase activity for A10B was 9.23 ± 0.02 U/mL and 15.36 ± 0.01 U/mL for B8A. The lowest enzyme activity was amylase, with 6.56 ± 0.003 U/mL and 3.17 ± 0.001 U/mL, respectively, for A10B and B8A. Under optimised conditions (55 ± 5 % moisture content, pH 7.5 ± 0.5), the isolates were tested for their PLA biodegradability in soil for a duration of 8 weeks. The biodegradation test of PLA buried in soil inoculated with isolate A10B recorded a weight loss of 32.6%, while isolate B8A recorded a weight loss of 37.8% from the initial PLA weight. These PLA samples were sent for SEM analysis and compared to the initial film, which showed decomposition signs on the PLA surface, therefore proving the ability of both isolates to degrade PLA in buried soil. In conclusion, this research demonstrates that both bacteria Brevibacillus parabrevis and Renibaterium salmoninarum have the potential to degrade PLA at mesophilic temperatures, which suggests that further research in this field may help develop novel bioremediation techniques, enhance current methods, and develop new pathways for recovering PLA polymers using bacteria.